MODELING AND SIMULATION AS MULTI-BODY SYSTEM OF A COMPLEX WINDSHIELD WIPER MECHANISM FOR MOTOR VEHICLES - Alexandru, Cătălin (My University, 2018)
Once with the advent of MBS (Multi-Body Systems) software solutions, the design of mechanical systems has evolved into a new direction: the modeling and simulation of complex virtual prototypes, close to the real products both in terms of system structure and operating conditions. Accurate virtual prototypes can be built on MBS platforms with the aim to minimize the costs that would result from the experimental testing of physical prototypes. The application corresponds to a complex windshield wiper mechanism that ensures a planar motion of the wiping lamella, thus increasing the cleaned surface of the windscreen. The mechanism is defined as a multi-body system with minimum number of bodies, with the aim to reduce the complexity of the virtual model. The kinematic simulation is carried out in virtual prototyping environment, by using the MBS software solution ADAMS.